A great master and his indispensable work: Manoel Bomfim (1868-1932) and O Brasil na Historia (1931) - Tonon, Marina [UNESP] (2017)
The present article tries to analyze the way in which the book Brasil na Historia, by Manoel Bomfim, was read and commented in the period of its release. Therefore, we will consider some texts published in Brazilian prominent newspapers. These works were written by important thinkers of the period that, formulating their texts, also produced certain image of the book and of its author. The investigation of these sources allowed to notice the book as a fundamental accomplishment for the national thought and Manoel Bomfim as a great thinker and Brazilian master.